Piperazinylpyrimidine modified MCM-41 for the ecofriendly synthesis of benzothiazoles by the simple cleavage of disulfide in the presence of molecular O21. Issue 89 (27th September 2015) - Ray, Suman; Das, Paramita; Banerjee, Biplab; Bhaumik, Asim; Mukhopadhyay, Chhanda
<x xml:space="preserve">Abstract</x> Synthesis of benzothiazoles by metal free cleavage of disulfide bond.